Recursive estimation of piecewise constant volatilities - Davies, Davies; Höhenrieder, Christian; Krämer, Walter (Technische Universität Dortmund, 2009)
Returns of risky assets are often modelled as the product of a volatility function times standard Gaussian noise. This paper proposes a piecewise constant volatility function and shows how to construct such functions so that (i) the number of intervals of constant volatilities is minimized, and that (ii) these constant volatilities are equal to the root mean squared returns.
Discussion Paper / SFB 823; 2/2009
Keywords: 310; 330; 620